Pemerkasaan wanita menurut perspektif hadis: Satu sorotan literatur - Muhammad Adam Abd. Azid; Najah Nadiah Amran; Hamdi Ishak (Universiti Sains Islam Malaysia, 2025)
Ulum Islamiyyah, Volume 37 Issue 01 Page (26–38)